2021
DOI: 10.1177/17588359211029559
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker evaluation in radically resectable locally advanced gastric cancer treated with neoadjuvant chemotherapy: an evidence reappraisal

Abstract: Neoadjuvant chemotherapy (NAC) significantly improved the prognosis of patients with locally advanced resectable gastric cancer but, despite important progresses, relapse-related death remains a major challenge. Therefore, it appears crucial to understand which patients will benefit from peri-operative treatment. Biomarkers such as human epidermal growth factor receptor-2 (HER2), microsatellite instability (MSI), and Epstein-Barr Virus (EBV) have been widely studied; however, they do not yet guide the choice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…In Caucasian patients data on pharmacogenetics (metabolism of 5-FU/oxaliplatin) (Smyth et al 2017 ; Ott et al 2006 ), tumor suppressor gene p53 and the transcription factor NF-kB, the cell cycle regulating protein p21, expression of tyrosine kinases (EGFR, Her2, c-Met) was associated with prognostic and/or predictive impact (Abdel-Latif et al 2004 ; Nakamura et al 2004 ; Ruhstaller et al 2018 ; Yamamoto et al 2017 ) However, these were often not done on pre-therapeutic biopsies or further confirming data were missing (Smyth et al 2017 ; Stahl et al 2018 ). Therefore, the identification of predictive markers in pre-therapeutic endoscopic tumor biopsies still is one of the urgent questions in upper gastrointestinal oncology and has been summarized in an overview recently (Gervaso et al 2021 ). Thus, we investigated the molecular background of 36 pre-therapeutic biopsies of AEG/AS patients, with opposite histopathologic response to standard neoadjuvant chemotherapy, for predictive molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…In Caucasian patients data on pharmacogenetics (metabolism of 5-FU/oxaliplatin) (Smyth et al 2017 ; Ott et al 2006 ), tumor suppressor gene p53 and the transcription factor NF-kB, the cell cycle regulating protein p21, expression of tyrosine kinases (EGFR, Her2, c-Met) was associated with prognostic and/or predictive impact (Abdel-Latif et al 2004 ; Nakamura et al 2004 ; Ruhstaller et al 2018 ; Yamamoto et al 2017 ) However, these were often not done on pre-therapeutic biopsies or further confirming data were missing (Smyth et al 2017 ; Stahl et al 2018 ). Therefore, the identification of predictive markers in pre-therapeutic endoscopic tumor biopsies still is one of the urgent questions in upper gastrointestinal oncology and has been summarized in an overview recently (Gervaso et al 2021 ). Thus, we investigated the molecular background of 36 pre-therapeutic biopsies of AEG/AS patients, with opposite histopathologic response to standard neoadjuvant chemotherapy, for predictive molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…In the postneoadjuvant therapy setting, although ypTNM and tumor regression grade (TRG) have been routinely examined in resected specimens, other prominent prognostic histopathological parameters are usually omitted, and clinical guidelines directing further management of these patients are still lacking[ 42 ]. Therefore, additional biomarkers with potential prognostic or predictive value in this specific condition are urgently needed to stratify patients into groups with different prognoses that may require different management.…”
Section: The Application Prospect Of Tb In Gcmentioning
confidence: 99%
“…The frequency of MSI-high GC reported in the literature has a considerable variation, ranging between 7% and 50%. Putative reasons for this variability include epidemiologic differences of enrolled patients in distinct cohorts (e.g., Asian versus Caucasian), inconstant tumor stage distribution between clinical trials, and differences in the methods used for investigating MSI or mismatch repair protein (MMR) status [5,[12][13][14][15][16][17][18]. However, recent studies from Europe and clinical trials have reported a lower percentage of MSI-high cases (6.6-11.7%) [12,13,[19][20][21][22][23], compared to the TCGA study in which MSI-high tumors accounted for 22% of cases [5].…”
Section: Introductionmentioning
confidence: 99%